Study of drug utilization in cardiovascular emergency at a rural teaching hospital in Tamilnadu, India - Fardan, Mohammed; Manjari, S.; Periasamy, S. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Cardiovascular disease is a common term which encompasses a range of disorders that affect the heart. Cardiovascular disease is the leading cause of death among men and women in India and across the globe. There is evidence of irrational drug use in cardiovascular disorders. Drug utilization study is used to evaluate the rationality of medication use. The objective of this study was to observe the most frequently treated emergency cardiovascular diseases and to study the prescribing pattern among inpatients admitted in CICU Unit of tertiary care teaching hospital. Methods: A retrospective, observational drug utilization study was designed to evaluate the drug prescribing pattern in cardiovascular emergency patients admitted in CICU unit of tertiary care teaching hospital. Study was carried out for a duration of 4 months. Data were collected from patient case reports after getting permission from Medical superintendent of hospital. Prescribing pattern of drugs were studied based on WHO indicators. Results: Total 150 patients were included in the study. Most common cardiovascular emergency reported was Myocardial infarction (60.66%) followed by Angina pectoris (24.66%). The most common comorbidities found along with cardiovascular emergency were hypertension (62.66%) followed by Diabetes mellitus (15.33%). Most prescribed cardiovascular drugs were from the category of hypolipidemics (94.66%) and anti-platelets (92.66%). Average number of drugs per prescription was found to be 9.42. Average hospital stay per patient was found to be 4.25 days. Percentage of drugs prescribed by generic name was 70.66%. Percentage of drugs prescribed from essential drug list and National list of essential medicines were 87.4% and 97.23% respectively. Conclusions: All the drugs prescribed were according to the current guidelines. Majority of the drugs were prescribed in generic form.